PENGGUNAAN DAN MAKNA JOSHI {~SAE} DAN {~MADE} DALAM KOMIK BAKUMAN KARYA TSUGUMI OHBA DAN TAKESHI OBATA - Ratnayanti Sukma, Luh Putu; Widya Purnawati, Ketut; Budiana, I Made (Humanis, 2016)
This research is aimed to find out the using and meaning of particles  {~sae} and {~made} in Bakuman comic by Tsugumi Ohba dan Takeshi Obata. This research especially discusses about the using and  meaning of particles  {~sae} and {~made} in Bakuman comic by Tsugumi Ohba dan Takeshi Obata. The data were analyzed using qualitative analysis method. First, the data collection was done with the methods “simak”. The one that was already collected analyzed by a method of “agih”. Then the results of the analysis served by using the method “informal”. This research used the theory from Makino and Tsutsui (1995) and Verhaar (2010). The conclusion from this research is particle {~sae} can be used in the positive sentence , negative sentence , conditional sentence and unconditional sentence. Meanwhile particle {~made} only can be used in the positive sentence and unconditional sentence. The comparison between both particles is particle {~sae} had a narrower meaning scope than  particle {~ made } .